2014
DOI: 10.3109/08958378.2014.953276
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on refractory ceramic fiber (RCF) carcinogenicity: comparisons with other fibers

Abstract: In 2011, SCOEL classified RCF as a secondary genotoxic carcinogen and supported a practical threshold. Inflammation was considered the predominant manifestation of RCF toxicity. Intrapleural and intraperitoneal implantation induced mesotheliomas and sarcomas in laboratory animals. Chronic nose-only inhalation bioassays indicated that RCF exposure in rats increased the incidence of lung cancer and similar exposures resulted in mesothelioma in hamsters, but these studies may have been compromised by overload. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 161 publications
(212 reference statements)
0
34
0
1
Order By: Relevance
“…The 1995 study by Järvholm of workers in a factory producing rock wool indicated that there was an increasing relationship between the age of workers and pleural plaques in this cohort compared to the occurrence of pleural plaques in non-exposed referents, although the differences were not statistically significant. Sandén & Järvholm (1986) determined that for all worker groups (exposed to what they identified as man-made mineral fibers -probably mineral wool) with at least 20 years of employment at shipyards the rate ratio for prevalence of pleural plaques was 1.4 [CI ¼ 1.1-1.8], although several epidemiological studies (Boffetta et al, 2014;Greim et al, 2014) indicate that exposure to mineral wool is not associated with an increase in rates of lung cancer or mesothelioma. Studies (Lockey et al, 1996) have indicated that exposure to refractory ceramic fibers is associated with an increase in pleural plaques, but the available evidence (Greim et al, 2014;LeMasters et al, 2003) suggests that exposure to RCF is not associated with any increase in lung cancer or mesothelioma.…”
Section: Findings Of External Review Groups/agenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1995 study by Järvholm of workers in a factory producing rock wool indicated that there was an increasing relationship between the age of workers and pleural plaques in this cohort compared to the occurrence of pleural plaques in non-exposed referents, although the differences were not statistically significant. Sandén & Järvholm (1986) determined that for all worker groups (exposed to what they identified as man-made mineral fibers -probably mineral wool) with at least 20 years of employment at shipyards the rate ratio for prevalence of pleural plaques was 1.4 [CI ¼ 1.1-1.8], although several epidemiological studies (Boffetta et al, 2014;Greim et al, 2014) indicate that exposure to mineral wool is not associated with an increase in rates of lung cancer or mesothelioma. Studies (Lockey et al, 1996) have indicated that exposure to refractory ceramic fibers is associated with an increase in pleural plaques, but the available evidence (Greim et al, 2014;LeMasters et al, 2003) suggests that exposure to RCF is not associated with any increase in lung cancer or mesothelioma.…”
Section: Findings Of External Review Groups/agenciesmentioning
confidence: 99%
“…Sandén & Järvholm (1986) determined that for all worker groups (exposed to what they identified as man-made mineral fibers -probably mineral wool) with at least 20 years of employment at shipyards the rate ratio for prevalence of pleural plaques was 1.4 [CI ¼ 1.1-1.8], although several epidemiological studies (Boffetta et al, 2014;Greim et al, 2014) indicate that exposure to mineral wool is not associated with an increase in rates of lung cancer or mesothelioma. Studies (Lockey et al, 1996) have indicated that exposure to refractory ceramic fibers is associated with an increase in pleural plaques, but the available evidence (Greim et al, 2014;LeMasters et al, 2003) suggests that exposure to RCF is not associated with any increase in lung cancer or mesothelioma. The available evidence fails to indicate that there is a consistent relationship between pleural plaques and either lung cancer or mesothelioma in cohorts that have developed pleural plaques when occupationally exposed to these other fibers.…”
Section: Findings Of External Review Groups/agenciesmentioning
confidence: 99%
“…Asbestos production and trade is prohibited in some countries, while others have maintained or increased production and use in recent years. Substitution of asbestos by artificial fibers would not necessarily lower or eliminate health risks [10][11][12][13]96,97]. The increased incidence of malignant Mt in developed nations [98,99], despite the prohibition of asbestos, is probably at least in part due to improved diagnostics, an increasing awareness of Mt, a screening effect in asbestos-exposed populations, and some over-diagnosis in conditions with an unclear demarcation of malignant Mt as an entity.…”
Section: Resultsmentioning
confidence: 99%
“…It can be spontaneous, or occur when asbestos fibers are present in the pulmonary or pleural tissues. Apart from asbestos, other potential etiologic factors of malignant Mt are mineral (erionite) and artificial (ceramic, carbone nanotubes) fibers [10][11][12][13], virus SV40, radiation, and genetic predisposition [14][15][16][17] (Figure 2). …”
mentioning
confidence: 99%
“…However, fibres are not suitable for application in environments with very high gas velocities or in contact with certain molten metals or glasses. A known disadvantage of some types of glass fibres is the health hazards associated with them [8][9][10]. Conventional fibre insulation materials are commonly known as refractory ceramic fibres (RCF), and these fibres are classified as category 1A or 1B (definite and possible human carcinogen, respectively) [11,12].…”
Section: Commercial Materialsmentioning
confidence: 99%